N‐glycosylation and expression in human tissues of the orphan GPR61 receptor. Issue 12 (20th November 2017) - Kozielewicz, Paweł; Alomar, Hatun; Yusof, Syaratul; Grafton, Gillian; Cooper, Alison J.; Curnow, S. John; Ironside, James W.; Pall, Hardev; Barnes, Nicholas M.
Abstract : A number of members of the G protein‐coupled receptor class of cell surface receptors are 'orphans' with no known endogenous ligand. One of these orphan receptors is GPR61; there are little data about its expression in human cells and tissues. In this study, we investigated the post‐translational modification of GPR61 by N‐ glycosylation at an identified consensus N ‐glycosylation site (N12) and the impact of this modification upon the subcellular expression of the protein. The N ‐glycosylation inhibitor tunicamycin reduced the apparent molecular weight of immunoreactivity associated with myc ‐tagged GPR61 by 1–2 kDa, which was comparable to the evident molecular weight of the myc ‐tagged N12S GPR61 mutant with disrupted consensus N ‐glycosylation site. Analysis of GPR61 expression demonstrated that tunicamycin treatment reduced considerably heterologous expression of GPR61 in the cell membrane despite the N12S GPR61 mutant being readily expressed at the cell surface. These results demonstrate that GPR61 is subject to N ‐glycosylation but suggest this is not a prerequisite for cell surface expression, although N‐ glycosylation of other proteins may be important for cell membrane expression of GPR61. Expression of GPR61 protein was demonstrated at the cellular level in human hippocampus and human peripheral blood mononuclear cells. In the latter, there was a significantly higher expression of GPR61 in the Th17 cell subset in comparison with resting CD4+ cells, which may point toward a potential role for the GPR61 receptor in autoimmune diseases. This is the first report that GPR61 protein is subject to post‐translational modification and is expressed in immune cell subsets and the hippocampus. These findings will help guide studies to investigate the function of GPR61. Abstract : In this study, we investigated the N‐ glycosylation and expression levels of the orphan receptor GPR61. We demonstrate that this G protein‐coupled receptor is N ‐glycosylated but this post‐translational modification is not a prerequisite for the membrane expression of the receptor. We also report that expression levels of GPR61 in peripheral blood mononuclear cells are significantly higher in Th17 cells than in resting CD4+ cells.